Closeness to God, Spiritual Struggles, and Wellbeing in the First Year of College - Gilbertson, Madison Kawakami; Brady, Shannon T.; Ablorh, Tsotso; Logel, Christine; Schnitker, Sarah A. (Frontiers in Psychology, 2022)
Spirituality is an important, but oft-overlooked, aspect of the self that may affect college students’ wellbeing and belonging. Few studies have systematically examined closeness to God and spiritual struggles as predictors of college student wellbeing during early college, which is a critical window for identity development. Moreover, research exploring interactions between spiritual struggles and closeness to God in predicting wellbeing outcomes is scarce. We address these gaps in the literature with an analytic sample comprised of 839 first-year college participants who identify as religious. The results of correlational analyses and linear mixed effect models are presented. Closeness to God was associated with greater wellbeing and belonging, and spiritual struggles were associated with lower wellbeing and belonging. In exploratory analyses, a moderating effect of closeness to God on the relation between spiritual struggles and negative outcomes was observed. Implications for higher education and college student development are discussed.